State Policy in the Sphere of Family in Kazakhstan: Socio-Political Aspect - Yermekbaeva, Е.О.; Zhanpeiissova , К.Д.; Tashtemkhanova, Р.М. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
In recent years, the topic of state family policy has attracted increasing attention from researchers worldwide, especially in the context of globalization. Although this field remains relatively underexplored in Kazakhstan, there is a growing demand within the academic community to address family-related issues. Today, family and demographic challenges represent crucial areas for social and public policy, requiring careful scholarly focus. Special attention should also be paid to the stability of the modern family, including divorce dynamics, social and regional typologies, and underlying causes. This article analyzes the socio-political aspects of the family institution in the Republic of Kazakhstan. The study is based on official statistical data, government programs, and sociological research findings. It explores the transformation dynamics of family structures, identifies factors contributing to the decline in marriage rates, evaluates state support mechanisms, and examines the influence of gender roles and societal values. Additionally, the paper reviews key legislative acts aimed at protecting family rights, preventing domestic violence, improving the social status of family members, and strengthening the family institution. The analysis also considers the impact of globalization and urbanization on contemporary family configurations in Kazakhstan. The proposed recommendations offer a foundation for enhancing the effectiveness of state family policy, improving family welfare, safeguarding women's and children's rights, and fostering a more stable and harmonious family environment across the country.